Get vaccinated or else…employees’ perspective on mandatory vaccination in the retail sector in Zimbabwe - Mapuranga, Martha; Maunganidze, Farai; Ruggunan, Shaun (Frontiers in Psychology, 2022)
The emergence of COVID-19 has resulted in many changes in the world of work. Measures such as remote working, physical distancing, compulsory use of face masks, sanitization among others. With time, a number of medical interventions to deal with the pandemic were developed and availed. Zimbabwe’s retail sector was not spared of different vaccines which were meant to curb the virus. Most Zimbabwean organizations made it mandatory for their employees to get vaccinated or risked losing employment. However, less is known about the perceptions of employees toward voluntary vaccination. This gap is important given the strategic nature of employees in an organization. This paper poses the following questions (1) to what extent were employees consulted on the compulsory vaccination? (2) What are the employees’ perceptions toward compulsory vaccination? (3) How are employees coping with the mandatory vaccination? The study was premised on the classical work of Kurt Lewin on types of leadership, specifically autocratic-democratic styles. Twenty shopfloor employees from two major retail outlets with functional human resource departments and works councils in Masvingo were purposively sampled and interviewed using a semi-structured interview guide. The sample composed of women and men of different age groups. Thematic analysis was used to analyze data. The paper argues that employees have a right to be involved in issues that concern them. The study has established four levels of consultation existing on a continuum namely formal and genuine consultations, formal but less genuine consultations, informal consultations, and no consultation at all. The fourth level emerged to have been the most popular among most participants. With regards to employees’ perceptions of mandatory vaccination by management, findings have revealed three categories which are, perceived good decision, perceived tight hands on the part of management and the them and us perceptions. Concerning reactions to mandatory vaccination, the study has shown that employees in the retail sector had a number of options to follow. Some went for full vaccination willingly or under duress, while others settled for a single dose. Most participants highlighted that they fraudulently obtained some vaccination cards. These findings support the relevance of engaging employees on matters that affect them. The study has therefore established the importance of genuine consultations between management and employees on issues that pertains the latter.